Copolymerization of (2-phenyl-1,3-dioxolane-4-yl)methyl methacrylate with alkyl methacrylates: Reactivity ratios and copolymer characterization - Coskun, M; Ilter, Z (John Wiley & Sons Inc, 2002)
The radical copolymerizations of (2-phenyl-1,3-dioxolane-4-yl-)methyI methacrylate (PDMMA) with methyl methacrylate (MMA), ethyl methacrylate (EMA), and butyl methacrylate (BMA) were studied in dioxane at 60 degreesC with benzoyl peroxide as an initiator. The glass-transition temperatures of poly(PDMMA-co-MMA), poly(PDMMA-co-EMA), and poly(PDMMA-co-BMA) varied from 130 to 138 degreesC, from 100 to 134 degreesC, and from 63 to 122 degreesC, respectively, depending on the copolymer composition. Along with some physicochemical properties and thermal stability investigations of the copolymers, the monomer reactivity ratios were also determined with the conventional Finemann-Ross and Kelen-Tudos linearization methods. (C) 2002 Wiley Periodicals, Inc.
Keywords: alkyl methacrylate; reactivity ratio; glass-transition temperature